Biodiversity conservation and ecological value of protected areas: a review of current situation and future prospects - He, Xiangyu; Wei, Hongbin (Frontiers in Ecology and Evolution, 2023)
The establishment of protected areas (PAs) is an effective way to biodiversity conservation while maintaining the multiple functions of ecosystem services. However, there is still a lack of comprehensive analysis on the relationship between PAs, biodiversity conservation, and ecological value in the field of research on prospects. Therefore, based on the research progress of literature content, this paper systematically reviews and evaluates domestic and international studies in terms of the biodiversity conservation and the ecological value of PAs. The results showed that relevant studies in recent years have mainly analyzed the spatial layout, area changes and conservation effectiveness of PAs in relation to biodiversity; By constructing the connotation system of ecological value concept of PAs, the research progress of ecological value accounting, ecological value realization and transformation, and ecological value types of PAs is further discussed, and the prospects of biodiversity conservation and ecological value research of PAs is proposed. This study provides a reference for the implementation of the Kunming-Montreal Global Biodiversity Framework and the construction and optimization of PAs system.